Increased biomass of free-living marine nematodes may be indicative of disturbances in the ecosystem of the San Antonio Bay - Gabriela Villares; Catalina Pastor de Ward (Open Journal of Environmental Biology - Peertechz Publications, 2020)
An ecological study of free-living marine nematodes in salt marshes of San Antonio bay was carried out to determine whether they are affected by anthropic disturbances. Samples were collected during the summer of 2009. Three sites were selected, one with urban disturbance and two with possible control. In each site the samples were taken in the 3 areas of the mesolittoral. Nematodes were separated, counted, measured and identified at species level. San Antonio bay presented high salinity values in all sites. "Ciudad" showed the highest values of heavy metals and nematode volumetric biomass. "Baliza Camino" presented the highest salinity values and the lowest volumetric biomass values. "Banco Perdices" presented low organic matter and values intermediate of volumetric biomass.  The result indicated that volumetric biomass acted as good indicator of the state of the bay, since the presence of high values of this nematodes would be contributing information about the presence of disturbances.